Transformation of the aggregate subject of activity in the context of digitalization of education - Terekhin, Vyacheslav; Korochentseva, Anna (E3S web of conferences, 2023)
The criteria for academic success are academic (educational) performance, reflecting the level of educational achievement, as well as interest, motivation, quality and methods of mental work (activity, tension, pace, duration, consistency, the ratio of rational and irrational methods of work, etc.). In our work, we examined how the above factors affect the success of students' learning activities in different forms of organizing the activities of the study group. Two main forms are considered: distance learning and full-time. The study allows us to trace the role of sociopsychological factors affecting the transformation of the aggregate subject of activity in the context of digitalization of education. The study involved two groups of university students. The first group: students of 1-4 courses, who have a distant form of organizing the activities of a group of 60 people. The second group: students of 1-4 courses, who have a full-time form of organizing the activities of a group of 60 people. The total sample size was 120 people. Methods used: Study method motivation learning at the university T.I. Ilyina; Test - questionnaire "Motivation for success and fear of failure" by AA Reana; Methodology studyingI social and psychological self-assessment of the team of O. Nemov; Questionnaire for the diagnosis of the ability to empathy. The research carried out confirms the proposed assumption that the form of organization of the group's activities significantly affects the success of its educational activities. Therefore, we can say that students with a full-time form of organizing activities are more successful in their educational activities than students with a distant system, since they strive to a significant extent to gain knowledge, master a profession, achieve success, and be within the team. to share his interests, to maintain friendly and comradely relations with each other than students with a distant form of organization of activities, who strive to be outside the team, since they may regard their classmates as potential competitors who can hinder the achievement of success in their educational activities.